3-O-Ethyl Ascorbic Acid and Cannabigerol in Modulating the Phospholipid Metabolism of Keratinocytes - Iwona Jarocka-Karpowicz; Izabela Dobrzyńska; Anna Stasiewicz; Elżbieta Skrzydlewska (MDPI AG, 2024)
Phospholipids and their metabolites play an important role in maintaining the membrane integrity and the metabolic functions of keratinocytes under physiological conditions and in the regeneration process after exposure to high-energy UVB radiation. Therefore, in the search for compounds with a protective and regenerative effect on keratinocyte phospholipids, the effectiveness of two antioxidant compounds has been tested: a stable derivative of ascorbic acid, 3-O-ethyl ascorbic acid (EAA) and cannabigerol (CBG), both of which are primarily located in the membrane structures of keratinocytes. In addition, this study has demonstrated that EAA and CBG, especially in a two-component combination, enhance the antioxidant properties of keratinocytes and reduce lipid peroxidation assessed at the level of MDA (malondialdehyde)/neuroprostanes. Moreover, by reducing the activity of enzymes that metabolise phospholipids, free PUFAs (polyunsaturated fatty acids) and endocannabinoids (PLA2; phospholipase A2, COX1/2; cyclooxygenases 1/2, LOX-5; lipoxygenase 5, FAAH; fatty acid amide hydrolase, MAGL; monoacylglycerol lipase), antioxidants have been found to regulate the levels of endocannabinoids (AEA; anandamide, 2-AG; 2-arachidonoylglycerol, PEA; palmitoylethanolamide) and eicosanoids (PGD2; prostaglandin D2, PGE2; prostaglandin E2, 15-d-PGJ2; 15-deoxy-Δ12,14-prostaglandin J2, 15-HETE; 15-hydroxyeicosatetraenoic acid), that are enhanced by UVB radiation. The metabolic effect of both groups of PUFA metabolites is mainly related to the activation of G protein-related receptors (CB1/2; cannabinoid receptor 1 and 2, PPARγ; peroxisome proliferator-activated receptor gamma, TRPV1; transient receptor potential cation channel subfamily V member 1), the expression of which is reduced under the influence of EAA, CBG, and especially the two-component combination. It promotes the regeneration of keratinocyte metabolism disrupted by UVB, particularly in relation to redox balance and inflammation.